New Technologies and Not-So-New Democracies - Schudson, Michael (MedieKultur: Journal of media and communication research, 2006)
Discussions of the impact of the new media on democratic politics often generalize too broadly about new technologies and almost always take for granted a uniformity about democracies. Democra- cies vary across nations and over time. For the USA, it is argued that Americans have had four different visions of what political spe- ech and participation should be. American democracy has shifted from a citizenship of deference, to one of party enthusiasm, to a model of the informed citizen, to the contemporary model of irreve- rent citizenship. Each model calls forth different versions of a public sphere. What is the democracy that technology is having an impact on? This question must be integrated in the discussion of the impact of technology on democracy.